Theoretical and experimental study of turbine flowmeters - Xu, Y. F. (Cranfield University, 2015)
A vortex shedding model is developed to predict the flow fields around turbine flowmeter blades. This model is used to simulate the flow separation and reattachment in the leading edge areas and the wake flows of the blades. Lewis's inverse blade design method is developed and quite successfully applied to simulate the displacement effect of the separation bubbles in the leading edge areas. A new method is introduced to apply the Kutta condition in unsteady flows around the blades wi th separation points on a blade surface or the flow with blade interaction. This method does not require a large amount of iterative calculation. A model is built up to predict the turbine flowmeter performance when the inlet flow conditions are known. The panel method is applied to predict the inlet flow conditions for the cases without inlet swirl. An experimental study of the flow inside a turbine flowmeter is carried out using Laser Doppler Anemometry(LDA) to measure the throughout velocity fields around a flowmeter at different flowrates and with different inlet swirls. A clear picture of the flow field is thus obtained. The measured resul ts are also used to validate the developed turbine flowmeter performance prediction model. The numerical prediction are tested with experimental results. The theoretical and experimental data agree with each other very well in the cases without inlet swirl and reasonably ",ell in other tested cases with inlet swirl.